Disulfide-crosslinked nanomicelles confer cancer-specific drug delivery and improve efficacy of paclitaxel in bladder cancer. (19th September 2016) - Pan, Amy; Zhang, Hongyong; Li, Yuanpei; Lin, Tzu-yin; Wang, Fuli; Lee, Joyce; Cheng, Mingshan; Dall'Era, Marc; Li, Tianhong; deVere White, Ralph; Pan, Chong-Xian; Lam, Kit S
Abstract: Chemotherapy commonly used in the treatment of advanced bladder cancer is only moderately effective and associated with significant toxicity. There has been no appreciable improvement in overall survival over the last three decades. The goal of this project is to develop and characterize bladder cancer-specific nanometer-scale micelles loaded with the chemotherapeutic drug paclitaxel (PTX) and determine the anti-tumor activity and toxicity. Micelle-building-material telodendrimers were synthesized through the stepwise conjugation of eight cholic acid units at one terminus of polyethylene glycol (PEG) and a bladder cancer-specific targeting peptide named PLZ4 at the other terminus. To synthesize disulfide-crosslinked PLZ4 nanomicelles (DC-PNM), cysteine was introduced between the cholic acid and PEG. DC-PNM-PTX was synthesized through the evaporation method by loading PTX in the core. The loading capacity of PTX in DC-PNM was 25% (W/W). The loading efficiency was over 99%. DC-PNM-PTX was spherical with the median size of 25 nm. The stability of DC-PNM-PTX was determined in a solution containing sodium docecyl sulfate (SDS). It was stable in a SDS solution, but dissolved within 5 min after the addition of glutathione at the physiological intracellular concentration of 10 mM. In vivo targeting and anti-tumor activity were determined in immunodeficient mice carrying patient-derived bladder cancer xenografts (PDXs). After intravenous administration, DC-PNM specifically targeted the bladder cancer PDXs, but very little to the lung cancer xenografts in the same mice (p < 0.001). DC-PNM loaded with PTX overcame cisplatin resistance, and improved the median survival from 55 d with free PTX to 69.5 d (p = 0.03) of mice carrying PDXs. In conclusion, DC-PNM remained stable in the SDS solution, specifically targeted the bladder cancer xenografts in vivo, and improved the anti-cancer efficacy of PTX.